How countries manage reserve assets - Pringle, Robert; Carver, Nick; Royal Bank of Scotland (London : Central Banking Publications, 2003)
The book reports on how central banks individually are meeting the challenges of reserve assets management. While addressing the overarching questions of reserve management, reserve adequacy, intervention, allocation and diversification of assets, and management procedures. It draws on the specialist knowledge of reserve management practitioners from central banks across the economic spectrum, with differing perspectives and occassionally contrasting viewpoints.
"The Royal Bank of Scotland"--Cover.
Includes bibliographical references.
oif 16/10/14
Loan
Keywords: Bank reserves; Reserves (Accounting).; International liquidity; Banks and banking, Central; Reserve management; Foreign exchange .; Gold